A novel subdomain and magnetic circuit modeling method for hybrid homopolar radial magnetic bearings. (1st May 2022) - Yu, Chunmin; Deng, Zhiquan; Chen, Shangsi; Mei, Lei; Peng, Cong; Cao, Xin
Abstract: A homopolar radial magnetic bearing (HRMB) that rotor is solid is studied to analyze the differences of magnetic circuits that control flux in static and dynamic magnetic fields because of the eddy current effects. To forecast the characteristics of the HRMB, a novel subdomain and magnetic circuit modeling method are introduced. The static and dynamic characteristics of the HRMB are analyzed using a hybrid model that combines the magnetic circuit method (MCM) and the subdomain method. The magnetic field distribution, bearing capacity, and stiffness are calculated and validated with the finite element method (FEM). The subdomain method could be used to estimate the static control flux, whereas the combination of the subdomain method and the MCM is needed to determine the dynamic control flux accurately. The accuracy of the novel modeling method is significantly higher than the conventional only subdomain method used to calculate the dynamic control flux, and the computation speed of the method is dramatically faster than the FEM. The modeling method also has a considerable impact on the design of the controller. Ultimately, the accuracy of the hybrid model is verified by the experimental results.